Omaggio al disagio. Pedagogia ultima spiaggia? - Caligiuri, Mario (Studi sulla Formazione/Open Journal of Education, 2021)
The reflections on education represents the main political problem of democracies in the 21st century: they are in crisis mainly due to the (also educational) inadequacy of their elites. Therefore, education becomes the tool able to activate a social change and to provide cultural antibodies to deal with the dynamics that amplify social unease. This article proposes the thesis that pedagogy, overcoming inadequacy and self-referentially, can represent the “last chance” to enhance the human factor in our society and to face the intrusiveness of artificial intelligence.